Preparation, structural and microstructural characterization of Ti-25Ta-10Zr alloy forbiomedical applications - de Freitas Quadros, Fernanda (2019)
Titanium alloys are widely used in the biomedical field due to their good corrosion resistance, high mechanical strength/density ratio, low elastic modulus, and good biocompatibility. With the addition of β-stabilizers elements (such as tantalum), the decrease of the elastic modulus and excellent corrosion resistance are obtained. Zirconium despite being a neutral element appends a good corrosion resistance to titanium alloys. In this paper, Ti-25Ta-10Zr alloy was prepared and characterized aiming biomedical applications. Structural and microstructural analysis corroborated each other and showed the presence of characteristic peaks of three crystalline structures, hexagonal (α phase) and orthorhombic (α'' phase), dissolved in a matrix with body-centered cubic crystalline structure (β phase). In the indirect cytotoxicity test, no cytotoxic effects were observed on the produced alloy.